Rediscovering the roots and wonder of qualitative psychology in Spain: A cartographic exercise. Issue 3 (3rd July 2019) - Gemignani, Marco; Ferrari, Sara; Benítez, Isabel
ABSTRACT: After providing a short introduction to qualitative research in psychology in Spain, we report and interpret the results of an online survey in which 47 qualitative psychologists answered questions about their location, research topic, research group, and the strengths, limitations, and challenges of being a qualitative researcher in Spain. The participants enthusiastically endorsed the use of qualitative methodologies, which were especially praised for being able to bring researchers closer to the roots of psychology by acknowledging fundamental human processes such as interpretation, depth in data collection and analysis, research rapport, care, epistemological and cultural diversity, and commitment to social justice. They also pointed out some practical challenges related to methodological standardizations and feeling undervalued within Spanish psychology, which tends to be positivist, empiricist, and realist. Last, the participants provided specific suggestions to increase the knowledge, visibility, and appreciation of qualitative methodologies in psychology in Spain.